2017
DOI: 10.1073/pnas.1708206114
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aggregation states of light-harvesting complexes as a mechanism for modulating energy transfer in desert crust cyanobacteria

Abstract: In this paper we propose an energy dissipation mechanism that is completely reliant on changes in the aggregation state of the phycobilisome light-harvesting antenna components. All photosynthetic organisms regulate the efficiency of excitation energy transfer (EET) to fit light energy supply to biochemical demands. Not many do this to the extent required of desert crust cyanobacteria. Following predawn dew deposition, they harvest light energy with maximum efficiency until desiccating in the early morning hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…These cyanobacteria face extreme environments, including large temperature fluctuations and daily hydration/dehydration cycles (Murik et al, ). Desiccation‐tolerant cyanobacteria were suggested to have evolved a broad range of survival strategies to cope with these extreme conditions, including the accumulation of intracellular osmotic substances (Lebre et al, ), enhanced exopolysaccharide production and accumulation of secreted proteins in an immobilized matrix (Tamaru et al, ), and re‐modulation of energy transfer pathways by changing the states of light‐harvesting protein complexes (Bar Eyal et al, ). A better understanding of the environmental adaptations of desiccation‐tolerant cyanobacteria is relevant for developing drought‐tolerant plants and preventing desertification.…”
Section: Introductionmentioning
confidence: 99%
“…These cyanobacteria face extreme environments, including large temperature fluctuations and daily hydration/dehydration cycles (Murik et al, ). Desiccation‐tolerant cyanobacteria were suggested to have evolved a broad range of survival strategies to cope with these extreme conditions, including the accumulation of intracellular osmotic substances (Lebre et al, ), enhanced exopolysaccharide production and accumulation of secreted proteins in an immobilized matrix (Tamaru et al, ), and re‐modulation of energy transfer pathways by changing the states of light‐harvesting protein complexes (Bar Eyal et al, ). A better understanding of the environmental adaptations of desiccation‐tolerant cyanobacteria is relevant for developing drought‐tolerant plants and preventing desertification.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular nanotubes are among the most interesting and most investigated structures. They are present in several natural photosynthetic complexes, for instance in the Green Sulphur Bacteria [4][5][6][7][8][9][10][11] or in Phycobilisome Antennas [12][13][14][15]. They are also present in other biomolecular systems, for instance in Microtubules, which are fundamental biological structures, showing interesting similarities with photosynthetic Antenna complexes [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Green Sulphur bacteria are photosynthetic organisms which live in deep water where the sunlight flux is very low [5] and they are among the most efficient photosynthetic systems [6][7][8]. Similarly to other antenna complexes present in nature [12][13][14][15], they present a high degree of symmetry being arranged in nontrivial cylindrical structures with an ordered orientation of the molecule dipoles. We analyse both the wild type (WT) and the triple mutant type (MT), which have been recently investigated in [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…In the hydrated state, the negative peak at 660 nm corresponds to APC660 and it indicates EET transfer from CPC rods to APC660. A previous study (Bar Eyal et al 2017) showed that the excitation energy is quenched within CPC rods in the desiccated state, which is reflected by the positive peak at 660 nm in Fig. 3b.…”
Section: Resultsmentioning
confidence: 58%
“…Time-resolved fluorescence of the cells was recorded at room temperature using a picosecond streak-camera system (van Stokkum et al 2008) as reported before (Bar Eyal et al 2017;Ranjbar Choubeh et al 2018), using a time window of 800 ps. The frequency-doubled output of a Ti:sapphire laser (Coherent, Mira) (800 nm) was used to excite the samples at 400 nm.…”
Section: Time-resolved Measurements and Data Analysismentioning
confidence: 99%